COMPETITIVENESS OF INDONESIAN NON-HUMAN CONSUMPTION SEAWEED IN THE CHINA MARKET - Hendra Sudirman; Sitti Hadija Samual; Aldila Mawanti Athirah (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
China is the largest importer of seaweed globally, and Indonesia is one of the countries that exports seaweed to China. Other exporting countries such as Chile and Peru also supply seaweed to China. This study aims to analyze the competitiveness of Indonesian seaweed (HS 121229) in comparison to seaweed from other exporting countries and to investigate the demand for Indonesian seaweed and other seaweed-exporting countries in the Chinese market. The study utilized export data from exporting countries that supplied China's seaweed requirements between 2012 and 2021. Revealed Symmetric Comparative Advantage (RSCA) and Almost Ideal Demand System (AIDS) were used for data analysis. The findings revealed that Indonesian seaweed (HS 121229) has a comparative advantage in the Chinese market. However, Indonesian seaweed's comparative advantage is still lower than its competitors. The demand for Indonesian seaweed in the Chinese market is inelastic. Therefore, to increase Indonesian seaweed's export income, exports should be increased rather than lowering prices. To reinforce Indonesia's position in the Chinese seaweed market, Indonesia should collaborate with other exporting countries that complement Indonesia's efforts, such as Chile.